Tratamento de água de produção de petróleo visando o aproveitamento na obtenção de barrilha - Nunes, Shirlle Katia da Silva (2013)
The petroleum production is associated to the produced water, which has dispersed and dissolved materials that damage not only the environment, but also the petroleum processing units. This study aims at the treatment of produced water focusing mainly on the removal of metals and oil and using this treated water as raw material for the production of sodium carbonate. Initially, it was addressed the removal of the following divalent metals: calcium, magnesium, barium, zinc, copper, iron, and cadmium. For this purpose, surfactants derived from vegetable oils, such as coconut oil, soybean oil, and sunflower oil, were used. The investigation showed that there is a stoichiometric relationship between the metals removed from the produced water and the surfactants used in the process of metals removal. It was also developed a model that correlates the hydrolysis constant of saponified coconut oil with the metal distribution between the resulting stages of the proposed process, flocs and aqueous phases, and relating the results with the pH of the medium. The correlation coefficient obtained was 0.963. Next, the process of producing washing soda (prefiro soda ahs ou sodium carbonate) started. The resulting water from the various treatment approaches from petroleum production water was used. During this stage of the research, it was observed that the surfactant assisted in the produced water treatment, by removing some metals and the dispersed oil entirety. The yield of sodium carbonate production was approximately 80%, and its purity was around 95%. It was also assessed, in the production of sodium carbonate, the influence of the type of reactor, using a continuous reactor and a batch reactor. These tests showed that the process with continuous reactor was not as efficient as the batch process. In general, it can be concluded that the production of sodium carbonate from water of oil production is a feasible process, rendering an effluent that causes a great environmental impact a raw material with large scale industrial use